Mobile phone and internet access as correlates of healthcare decision-making participation among married mothers in northern Nigeria. - Kazeem, Azeez (Discover Public Health, 2026)
In northern Nigeria, husbands independently make 61.1% of healthcare decisions, severely limiting mothers' participation. Drawing on Communication Privacy Management Theory (CPMT), this study examines whether communication technology access is associated with married mothers' healthcare decision-making participation where cultural norms mandate collective decision-making. We hypothesized that technology access is positively associated with higher reported participation (H1), and that number of children contextualizes this relationship (H2). Secondary analysis of 2018 Nigeria Demographic and Health Survey data (N = 17,118) employed survey-weighted logistic regression to model reported healthcare participation (deciding alone or jointly with husband) across three groups: no technology access (reference), phone-only access, and combined phone-internet access. Combined access was significantly associated with higher participation (H1 supported), though the cross-sectional design permits correlational inference only. Number of children moderated the phone-only association (H2 partially supported) but not the combined access association. The findings suggest that women with mobile phone and internet access were more likely to report involvement in healthcare decisions, consistent with relative participation operating within culturally mandated co-ownership constraints. These findings carry implications for health policy discussions concerning women's decisional participation in patriarchal contexts.